Comparing sleep disorders in urban and suburban adolescents - Nur'aini Nur'aini; Sri Sofyani; Supriatmo Supriatmo; Iskandar Z. Lubis (Indonesian Pediatric Society, 2014)
Background Sleep disturbances commonly occur in adolescents. Socioeconomic levels, lifestyle, and urban or suburban environments influence the sleep patterns of adolescents. The modernization process in urban environments is marked by the development of information technology media, and the lack of parental monitoring potentially influencing adolescent sleep disturbances. Sleep disturbances may affect children's physical growth, as well as their emotional, cognitive, and social development.Objective To assess for sleep disorders in urban and suburban adolescents, and to determine the factors that influence the prevalence of sleep disturbances.Methods A cross-sectional study was conducted on 12 to 15-year-old junior high school students in urban (n=350) and suburban (n=350) environments in the city of Medan, North Sumatera. The study was undertaken from May to June 2010 using the Sleep Disorders Scale for Children (SDSC), a set of questionnaires. The SDSC was filled out by parents based on what they remembered about their children's sleep patterns in the prior 6 months.Results In the urban group, there were 133 (38.0%) subjects with sleep disturbances, 182 (52.0%) were borderline, and 35 (10.0%) were normal. In the suburban group, there were 132 (37.7%) subjects with sleep disturbances, 180 (51.4%) were borderline, and 38 (10.9%) were normal. The most influential factors for sleep disturbances in urban and suburban youth were environmental noise (P=0.001) and consuming beverages that contain caffeine (P=0.001). There were three types of sleep disorders that significantly found more in urban adolescents: disorders of initiating and maintaining sleep, disorders of excessive somnolence, and sleep hyperhidrosis.Conclusion The prevalence of sleep disturbances do not differ between urban and suburban adolescents. Howevet; there are significant differences in the types of sleep disorders experienced. The most influential factors on sleep disturbance in both areas are environmental noise and consuming beverages that contain caffeine. Â